Effets de seuil dans la relation entre tourisme et croissance économique dans les pays membres de l’organisation des Etats de la caraïbe orientale (OECO) - Louis Dupont (Études Caribéennes)
This study applies a threshold regression model and considers one tourism specialization indice as the threshold variable in order to explore the nonlinear relation among tourism growth, economic growth, and other macroeconomic variables for a cross-sectional data set of six countries of Organization of Eastern Caribbean States (OECS). The main purpose of this paper is to analyse threshold effects of tourism receipts/PIB on economic growth in OECS zone countries. To achieve this, the study used Hansen’s Threshold Auto Regressive model (TAR), 1999. Our empirical results show strong evidence of a nonlinear relation between tourism growth and economic growth, with a unique threshold which is 25.27% GDP. Its marginal effect is 0.17 point, ‘all things being equal to otherwise’.